Seismic Performance of Base-Isolated Precast Concrete Shear Wall Structure with AHW Connections - Wei Wang; Aiqun Li; Xingxing Wang (Shock and Vibration)
To improve the seismic performance and seismic reliability of precast concrete shear wall (PCSW) structure with improved assembly horizontal wall connections (AHW connections), base isolation technology was proposed to be applied in the PCSW structure. Two 1/4-scaled structure models using the improved AHW connections were constructed: a lead-rubber bearing (LRB) base-isolated PCSW structure model and a base-fixed PCSW structure model. Shaking table tests were conducted on these two models with three strong ground motions to assess the seismic performance of the structures. It was found that the improved AHW connections in the base-isolated PCSW structure are useful and effective and that they fulfil the requirements to be met by the connections to withstand an earthquake. In addition, the maximum absolute acceleration and base shear force of the base-isolated PCSW structure model were less than those of the base-fixed PCSW structure model, and the isolation effect on the absolute acceleration responses and base shear responses increased with increase in the intensity of ground motions. In a word, the seismic performance and seismic reliability of PCSW structures can be effectively improved using base isolation technology. After this investigation, the seismic responses of the base-isolated PCSW structure model were numerically simulated using OpenSees software. There was a reasonable agreement between the numerically simulated results and test results; thus, the numerical simulation method and analysis model used for the base-isolated PCSW structure model were verified.